Teaching and Learning with Technology: Effectiveness of ICT Integration in Schools - Swarali Sanjay Shah (Indonesian Journal of Educational Research and Technology, 2022)
Integration of Information, Communication, and Technology (ICT) will assist teachers to the global requirement to replace traditional teaching methods with technology-based teaching and learning tools and facilities. In Malaysia, ICT is considered as one of the main elements in transforming the country to future development. The Ministry of Education, through the latest Education Blueprint (2013-2025), insights the importance of technology-based teaching and learning into the schools’ national curriculum. This study aims to analyze teachers’ perceptions of the effectiveness of ICT integration to support the teaching and learning process in the classroom. A survey questionnaire was distributed randomly to a total of 101 teachers from 10 public secondary schools in Kuala Lumpur, Malaysia. The data for this quantitative research were analyzed for both descriptive and inferential statistics using SPSS (version 21) software. The results indicate that ICT integration has great effectiveness for both teachers and students. Findings indicate that teachers’ well-equipped preparation with ICT tools and facilities is one of the main factors in the success of technology-based teaching and learning. It was also found that professional development training programs for teachers also played a key role in enhancing students’ quality learning. For future studies, there is a need for consideration of other aspects of ICT integration especially from a management point of view concerning strategic planning and policymaking.